Integration of Islamic Religious Education and Digital Technology in Shaping Students' IMTAQ Character in the Digital Age - Araniri, Nuruddin; Nahriyah, Syafa'atun (Indonesian Journal of Islamic Education, 2025)
Particularly in terms of forming students' Iman and Taqwa (IMTAQ), digital revolution in the era of Society 5.0 offers fresh opportunities and difficulties for Islamic religious education (PAI). In the middle of pervasive false information, moral deterioration, and poor digital ethics among students, the urgency of integration between Islamic beliefs and digital technology is becoming even more critical. This paper attempts to examine the combined model of Islamic education and digital technology in the development of students' IMTAQ character and highlight conceptual flaws in earlier studies. This study employs a qualitative technique applied in line with a literary study methodology. Content analysis was used to examine data gathered from pertinent scientific papers, books, and research reports released in 2019–2020. The results reveal that even with different digital innovations applied in PAI, integrated learning models, digital religious character evaluation, and parent and online community engagement still suffer gaps. This work practically provides a reference for curriculum creation and Islamic digital learning methodologies and theoretically in the form of issue mapping and preliminary design of the PAI-Technology-IMTAQ integrated model. This paper suggests the creation of digital media-based IMTAQ character evaluation tools and more experimental-based studies.